Pengaruh Pertumbuhan Laba, Firm Size dan Current Ratio terhadap Return Saham pada PT Bayan Resources Tbk Tahun 2014-2023 - Syahputra, Aldi Ibnu; Budi, Saksono (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
This study aims to determine the effect of Profit Growth, Firm Size, and Current Ratio on Stock Return at PT Bayan Resources Tbk during the period 2014-2023, both partially and simultaneously. The research method used is a quantitative approach. The population in this study is the financial statements of PT Bayan Resources Tbk. The sample used in this study consists of the financial statements of Bayan Resources Tbk for the period 2014-2023. The data analysis techniques used include Descriptive Analysis, Classical Assumption Test, Multiple Linear Regression Analysis, Correlation Coefficient Test, Determination Coefficient Test, and Hypothesis Testing. The results of the study show that the Profit Growth variable has a t-value of 1.635, which is smaller than the t-table value of 2.446 (1.635 < 2.446), and the significance level is greater than 0.05 (0.153 > 0.05), meaning that Profit Growth does not have an effect on Stock Return. Next, Firm Size shows a t-value of 5.008, which is greater than the t-table value of 2.446 (5.008 > 2.446), and the significance level (0.002 < 0.05), meaning that Firm Size has a positive effect on Stock Return. Meanwhile, the Current Ratio has a t-value of -1.576, which is smaller than the t-table value of 2.446 (-1.576 < 2.446), and the significance level is greater than 0.05 (0.166 > 0.05), indicating that the Current Ratio does not affect Stock Return. Furthermore, the simultaneous results show that Profit Growth, Firm Size, and Current Ratio significantly affect the Stock Return of PT Bayan Resources Tbk for the period 2014-2023, as evidenced by the F-value being greater than the F-table value (8.842 > 4.74).